The Analysis of Google Workspace for Education Implementation in Islamic Education Learning in Madrasahs - Mizan, Misbahul; Inayati, Nurul Latifatul (Universitas Muhammadiyah Surakarta, 2025)
The advancement of digital technology has brought significant changes in the world of education, including in learning Islamic Religious Education (PAI) in madrasah. One of the platforms that is widely used in supporting technology-based learning is Google Workspace for Education. This study aims to analyze the implementation of Google Workspace in Islamic Education learning in madrasah by looking at various educational institutions that have implemented it, with a library research approach. Data were collected from various academic journals and trusted sources to explore the benefits, challenges, and optimization strategies in using this platform. The results show that Google Classroom, Google Meet, Google Docs, Google Forms, and Google Drive have important roles in supporting more interactive and collaborative learning. However, some of the main challenges faced include limited internet access, lack of digital literacy among teachers and students, and constraints in online-based evaluation systems. Overcoming these obstacles requires continuous teacher training, provision of adequate infrastructure and development of learning methods that suit the needs of the madrasah. The implication of this study shows that the application of Google Workspace in PAI can improve learning effectiveness if supported by appropriate policies and adequate technological readiness. The results of this study are expected to be a reference for madrasahs in developing more effective and sustainable Islamic education digitization strategies. Keywords: Google Workspace for Education, Islamic Religious Education, Madrasah, Educational Technology, Digitalization of Learning.